Study the effect of thin film thickness on the optical features of (IR5 laser dye/CdSe nanoparticles) samples - Mithaq M. Mehdy Al-Sultani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The linear optical features such as (transmittance T, absorbance A, the effective length ????????????????, absorption coefficient ???? and refractive index ???? ) for the thin films samples of (3x10-3 mol/l of (IR5) laser dye, 0.02 gm of (CdS) nanoparticles and 0.04 gm of pp polymer) had been studied at different values of film thickness in one time and at different number of Yb:GdVO4 laser pulses. The non-linear optical features in terms of transmittance difference Δ????????−????, non-linear refractive index ????2, non–linear phase shift Δ???????? non-linear absorption coefficient ???? and minimum normalized transmittance ????(????) have been computed in relation to obtained normalized transmittance data from setup of Z-scan with open and closed apertures, calculated for (3x10-3 mol/l of (IR5) laser dye, 0.02 gm of (CdSe) nanoparticles and 0.04 gm of (pp) polymer) thin films at different values of film thickness at in one time and at different Yb:GdVO4 laser pulses. Thick films causes in deleting the non-linear effects generated by different layers. The (CdSe) nanoparticles leads to an absorption shifting of the wavelengths to lengthier wavelengths of red shift. So, this can be used in selecting the nanoparticles and medium with applicable exciting wavelengths. The film thickness and the laser pulses have the main effects in consolidating the Non-linear optical features.